Toward a maqāṣid-oriented framework: Qur'anic and Prophetic principles for addressing contemporary economic issues - Bayutama; Amirul Bakhri (PT Perfidia Akademia, 2026)
Contemporary economic developments have generated various challenges, including riba, cryptocurrency, zakāt, and gharar, which are generally examined separately, leaving the interrelationship of Qur'anic and Prophetic principles insufficiently explained within a unified conceptual framework. This study aims to analyze Qur'anic and Prophetic principles in addressing contemporary economic issues through a maqāṣid al-sharīʿah-oriented approach. A qualitative library research design was employed using content analysis and thematic analysis. The findings reveal that riba, cryptocurrency, zakāt, and gharar are interconnected through four fundamental principles: justice, transparency, social responsibility, and legal certainty and the protection of wealth, ultimately contributing to the realization of maqāṣid al-sharīʿah, particularly ḥifẓ al-māl. This study contributes by proposing an integrated conceptual model linking contemporary economic challenges, Qur'anic and Prophetic principles, and the objectives of Islamic law as an analytical framework for advancing Islamic economics research and practice. Abstrak Perkembangan ekonomi kontemporer menghadirkan berbagai persoalan, seperti riba, cryptocurrency, zakat, dan gharar, yang umumnya masih dikaji secara parsial sehingga belum menunjukkan keterkaitan prinsip-prinsip Al-Qur'an dan Hadis dalam satu kerangka konseptual yang utuh. Penelitian ini bertujuan menganalisis prinsip-prinsip Al-Qur'an dan Hadis dalam merespons isu-isu ekonomi kontemporer melalui pendekatan berbasis maqāṣid al-syarī‘ah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan yang dianalisis melalui content analysis dan thematic analysis. Hasil penelitian menunjukkan bahwa riba, cryptocurrency, zakat, dan gharar saling berkaitan melalui empat prinsip utama, yaitu keadilan, transparansi, tanggung jawab sosial, serta kepastian dan perlindungan harta, yang secara terpadu mendukung pencapaian maqāṣid al-syarī‘ah, khususnya ḥifẓ al-māl. Penelitian ini berkontribusi dengan menawarkan model konseptual terintegrasi yang menghubungkan tantangan ekonomi kontemporer, prinsip-prinsip Al-Qur'an dan Hadis, serta tujuan syariat sebagai kerangka analitis bagi pengembangan kajian dan praktik ekonomi Islam.